Gut microbes improve prognosis of Klebsiella pneumoniae pulmonary infection through the lung-gut axis - Tang, Yuxiu; Chen, Liquan; Yang, Jin; Zhang, Suqing; Jin, Jun; Wei, Yao (Frontiers in Cellular and Infection Microbiology, 2024)
Sepsis is one of the most important causes of death in critically ill patients and has a complex and varied pathogenesis; pneumonia is the most common cause of sepsis in clinical practice. The existence of the gut-lung axis points to a protective role that the gut microbes plays a vital role in the development of sepsis and in protecting against pneumonia and correlates with the prognosis of critically ill patients. Here, we found that in contrast to direct antibiotic treatment, faecal microbiota transplantation(FMT) improves the prognosis of mice with pneumonia-derived sepsis caused by Klebsiella pneumoniae by improving the structure of the gut microbes and increasing the level of beneficial metabolites, fatty acids and secondary bile acids, thereby reducing systemic inflammation, repairing the barrier function of alveolar epithelial cells, and alleviating pathological damage to the lungs. The combination of antibiotics with FMT significantly alleviates intestinal microbiota disorder, reduces the selection for drug resistance genes caused by antibiotics, and mitigates lung lesions; these effects are superior to those following antibiotic monotherapy.